USING MIND MAPPING TECHNIQUE TO IMPROVE STUDENTS' ABILITY IN READING DESCRIPTIVE TEXT :A Quasy-Experimental Study in One of Junior High Schools in Bandung - Intan Dwi Puspita, - (2012)
This research entitled "Using Mind Mapping Technique to Improve Students' Ability in Reading Descriptive Text (A Quasi Experimental Research at seventh grades students of one Junior High School in Bandung)" was to investigate whether or not mind mapping technique was effective in teaching reading descriptive text. Besides, this research was also aimed to find out advantages and disadvantages in using mind mapping technique in reading descriptive text. A quasi experimental with pretest and posttest group design was used in the research. Sample of the research was 70 students; each group consists of 35 people. There were two classes as the samples, 7.8 as the experimental group and 7.9 as the control group. Reading test, interview and class observation were used as the research instrument. The reading test data were analyzed quantitatively by using SPSS 17 for Windows, while the interviews and class observation data were analyzed qualitatively. From the findings, the result showed that mind mapping technique was effective in teaching reading descriptive text. The effectiveness could be seen from independent t-test computation which showed that t obtain value (4.602) was more than t critical value (1.96) at the level significance 0.05 (two-tailed) which indicated that the null hypothesis (H0) was rejected. Furthermore, the effectiveness was also supported by the students' responses from the interview. The students felt that mind mapping technique helped them understand the text easier, summarize and remember the information well, increase motivation, creativity and imagination. Meanwhile, the disadvantages of mind mapping technique in reading descriptive text were personal pictures/symbols that have understood by other students, time consuming, and media needed. This research recommended teachers to use mind mapping technique as an alternative media in teaching reading descriptive text. In addition, for further studies, it would be good if mind mapping technique is used in teaching reading other genres of texts.